Genomes of herbaceous land plants - Paterson, Andrew H., 1960- (Advances in botanical research, 2014)
Advances in Botanical Research publishes in-depth and up-to-date reviews on a wide range of topics in plant sciences. Currently in its 69th volume, the series features several reviews by recognized experts on all aspects of plant genetics, biochemistry, cell biology, molecular biology, physiology and ecology. This thematic volume features reviews on genomes of herbaceous land plants Publishes in-depth and up-to-date reviews on a wide range of topics in plant sciences Features a wide range of reviews by recognized experts on all aspects of plant genetics, biochemistry, ce.